The Economics of Marriage: Dotal Strategies in Bologna in the Age of Catholic Reform - Carboni, Mauro (The sixteenth century journal, 2008)
The Bolognese Monte del matrimonio addressed the difficult problem of giving girls with moderate means a chance to marry, thus saving the honor of their families, not merely by charitable benevolence but by active planning. Mixing credit and piety, the Monte was designed in an innovative fashion and differed substantially from other similar institutions. Unlike the many dowry funds which dispensed bequests, it was tailored to give the respectable poor an opportunity to invest at interest their own savings. Parents, relatives, and would-be sponsors were invited to plan ahead by opening accounts for daughters and needy girls in order to provide a dowry at a lower cost. The Monte would manage the investment and pay the dowry when the beneficiary would claim it. Working to shore up the endangered pillar of early modern Bolognese society, the family, the Monte contributed substantially to perpetuating a civic tradition of solidarity by updating and forging a solid network of bonds, which in turn helped to reduce, govern, and channel growing social tensions.